Pengaruh Kinerja Keuangan dan Makroekonomi Terhadap Harga Saham Sektor Industri Konsumsi - Tony Irawan, Nur M. Azizah, Lukytawati Anggraeni, (Jurnal Ekonomi, 2020)
Stock price can be affected by financial performance and macroeconomic. Investors need to consider financial performance and macroeconomic condition in making investment decision. The goal of this study is to analyze the effect of financial performance and macroeconomic toward stock price of consumer goods industry. Panel Data Regression is used in this study to analyze the effect of financial performance and macroeconomic toward stock price. The result of this study shows the liquidity ratio (CR) has a significant and negative effect toward stock price, while the profitability ratio (ROE) has a significant and positive effect toward stock price. Macroeconomic inflation and exchange rate have a significant and positive effect toward stock price. Firms with high liquidity ratio (CR) have to control the liquidity ratio, because in the long term high liquidity has a negative effect toward stock price so the stock price may decrease. Investors need to compare the financial performance in order to make a good decision.